Remembering the Liberation Struggles in Cape Verde A Mnemohistory - Cardina, Miguel (Memory Studies: Global Constellations, 2022)
Remembering the Liberation Struggles in Cape Verde: A Mnemohistory takes as its reference from the anti-colonial struggles against the Portuguese colonial empire in Africa in the 1960s and 1970s and the ways this period has been publicly remembered. Drawing on original and detailed empirical research, it presents novel insights into the complex entanglements between colonial pasts and political memories of anti-colonialism in shaping new nations arising out of liberation struggles. Broadening postcolonial memory studies by emphasising underdeveloped research cases, it provides the first comprehensive research into how the liberation struggle is memorialised in Cape Verde and why it changes over time. Proposing an innovative approach to thinking about this historical event as a political subject, the book argues that the ""struggle"" constitutes a mnemonic device mobilised while negotiating contemporaneous representations related to the Cape Verdean nation, state and society. As such, it will appeal to scholars of history, sociology, anthropology and politics with interests in memory studies and public memory, postcolonialisms and African studies.